The Role of Perceived Organizational Support Mediation in the Influence of Ethical Leadership on Employee Engagement - Melida Wijaya; Winda Nuraeni; Desiam Annisa Fitri Weni; Pupung Purnamasari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
Ethical leadership is a leadership style based on moral values, fairness, and integrity in the decision-making process, thereby creating positive working relationships between leaders and employees. Employee engagement is an important aspect in improving performance and achieving organizational goals. The level of employee engagement is not only influenced by the behavior of leaders, but also by the extent to which employees feel supported by the organization, known as perceived organizational support. This study is a literature review that aims to explain the mediating role of perceived organizational support in the influence of ethical leadership on employee engagement. The results of various studies show that ethical leadership has a positive influence on employee engagement, and this influence is stronger when employees feel a high level of organizational support. Perceived organizational support acts as a mediator that strengthens the relationship between ethical leadership and employee engagement. These findings emphasize the importance of organizations in building an ethical culture and ensuring tangible support to optimally increase employee engagement